Energieffektivt bageri - Lundberg, Emanuel (2016)
An energy audit of Polarbröds three bakeries in Älvsbyn, Bredbyn and Omne and a deeper energy analysis of the bakery in Älvsbyn have been made.The energy audit of the bakery in Älvsbyn showed that the factory had an average power consumption of 2 500 kW during production. The bakery has production nonstop from Sunday night until Friday night. In the weekend, when there is no production, the power consumption went down to 570 kW. The process with the highest energy use was the oven which used 56 % (9 400 MWh/year) of the total electricity. The process with the second highest energy use was the chilling plant which used 17 % (2 900 MWh/year). In the year 2014, the bakery used 16 600 MWh of electricity and 190 MWh of district heating. This amount of energy was used to produce 26 000 ton bread. The key figure for the energy use of the bakery is 0.64 kWh/kg produced bread.Previous results have shown that excess heat from the ovens could not easily be recovered. Therefore, in this thesis the focus has been on an energy optimization of the chilling plant and the ventilation system. In the year 2014 the factory had a total cooling energy demand of 3 000 MWh, where the production freezer and the storage freezer together used 2 300 MWh. The ventilation system had a cooling need of 700 MWh. To reduce the load of the chilling plant, a snow storage was designed with a storage capacity of 25 000 m3 at an investment cost of about 10 million SEK. Every year, the snow storage would decrease the total energy use with about 670 MWh and the cooling cost with 690 000 SEK. With a discount rate of 5 % the payback time is 14 years, while a discount rate of 10 % results in 35 years. The key figure for the energy use of the bakery will then drop to 0.61 kWh/kg produced bread. Validerat; 20151217 (global_studentproject_submitter)